Respuesta :
Answer:
[tex]\large\boxed{\boxed{x = \begin{cases} \frac{ \sqrt{3} }{2} + 2 \\ - \frac{ \sqrt{3} }{2} + 2 \end{cases}}}[/tex]
Step-by-step explanation:
to understand this
you need to know about:
- quadratic equation
- PEMDAS
let's solve:
- [tex] \sf divide \: both \: sides \: by \: 12 : \\ \sf {x}^{2} - 4x = - \frac{13}{4} [/tex]
- [tex] \sf \: add \: { - 2}^{2} \: to \: both \: sides : \\ \sf { {x}^{2} } - 4x + ( - {2}^{2} ) = -\frac{13}{4} + ( { - 2}^{2} ) \\ {x}^{2} - 4x + 4 = -\frac{13}{4} + 4[/tex]
- [tex] \sf simplify \: addition : \\ \sf { {x}^{2} } - 4x + 4 = \frac{3}{4} [/tex]
- [tex] \sf use \: {a}^{2} - 2ab + {b}^{2} = (a - b {)}^{2} : \\ \sf (x - 2 {)}^{2} = \frac{3}{4} [/tex]
- [tex] \sf squre \: root \: both \: sides : \\ \sf \sqrt{(x - 2 {)}^{2} } = \pm \sqrt{ \frac{3}{4} } \\ \begin{cases} x - 2 = \frac{ \sqrt{3} }{2} \\x - 2 = - \frac{ \sqrt{3} }{2} \end{cases}[/tex]
- [tex] \sf add \: 2 \: to \: both \: sides : \\ \sf \begin{cases}x = \frac{ \sqrt{3} }{2} + 2 \\ x = - \frac{ \sqrt{3} }{2} + 2 \end{cases} \\ \therefore \: x = \begin{cases} \frac{ \sqrt{3} }{2} + 2 \\ - \frac{ \sqrt{3} }{2} + 2 \end{cases}[/tex]
Answer:
[tex]x=\frac{4+\sqrt{3} }{2}[/tex]
[tex]x=\frac{4-\sqrt{3} }{2}[/tex]
Step-by-step explanation:
12x² - 48x = - 39
Add 39 to both sides.
12x² - 48x + 39 = 0
[tex]x = \frac{-(-48)±\sqrt{(-48)^{2}-4(12)(39) } }{(2)(12)}[/tex]
[tex]x=\frac{4+\sqrt{3} }{2}[/tex]
[tex]x=\frac{4-\sqrt{3} }{2}[/tex]